2008
DOI: 10.1080/09638280701532243
|View full text |Cite
|
Sign up to set email alerts
|

Women with Disabilities: Cultural competence in rehabilitation psychology

Abstract: Women with Disabilities represent a cultural group with specific issues. Rehabilitation psychologists are encouraged to familiarize themselves with some of those issues in order to deliver culturally relevant treatment. An overview is provided of psychological guidelines for attending to cultural issues in assessment, treatment, and research. Broad issues faced by Women with Disabilities are described. Disability-specific safety concerns are discussed with attention to ways in which they might be addressed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…The construct of cultural competence has received much attention in the psychological [1,2]; rehabilitation [3][4][5]; nursing [6][7][8]; and public health, educational and health professions literature [9,10], due in part to the increased diversity of the population in developed countries. In the USA, the most recent census figures suggest that about 30% of the population is of non-European Caucasian descent and that people of colour are becoming numerical majorities in some of the largest cities [11].…”
Section: Introductionmentioning
confidence: 99%
“…The construct of cultural competence has received much attention in the psychological [1,2]; rehabilitation [3][4][5]; nursing [6][7][8]; and public health, educational and health professions literature [9,10], due in part to the increased diversity of the population in developed countries. In the USA, the most recent census figures suggest that about 30% of the population is of non-European Caucasian descent and that people of colour are becoming numerical majorities in some of the largest cities [11].…”
Section: Introductionmentioning
confidence: 99%
“…44 When these two phenomena are considered together with the present results, it is clear that further research is needed in this area, and interventions designed according to detected needs would be extremely useful in improving QOL in these two social groups. 22,45,46 Of note is that the environmental dimension (safety, healthfulness, money, information, leisure, living conditions, health services, transport) exhibited no significant differences, suggesting that external resources met the needs and expectations of the surveyed patients. Previous research has found a significant association between satisfaction with external resources (for instance, health care) and QOL, 47 although no assumptions can be made about the directionality of this relationship.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, it is apparent that cultural issues, as discussed in the papers by Banks [6] and by Marshall, Kendall, Catalano & Barnett [7], affect individual views and relationships that largely determine the context within which a person performs tasks and engages in life situations and the opportunities available for Activities and Participation.…”
Section: Introductionmentioning
confidence: 97%